Cognate facilitation effect during auditory comprehension of a second language: A visual world eye-tracking study. (August 2022) - Andras, Filip; Rivera, Marta; Bajo, Teresa; Dussias, Paola E; Paolieri, Daniela
Aims and Objectives: The cognate facilitation effect (CFE) is a robust effect in language production and visual word comprehension, but evidence for CFE during auditory comprehension is still scarce. This study aimed to explore the CFE during auditory comprehension of a second language (L2) while manipulating proficiency in the L2 and cognate type. These two variables are known to influence the CFE. Methodology: Low and highly proficient Spanish–English bilinguals listened to individual words in their L2, English, that shared high, low, and no phonological overlap (PO) with their native language Spanish. We designed a visual world paradigm task that consisted of selecting an image shown as a spoken word unfolded in time while eye movements were recorded. Data and Analysis: Response times revealed a clear CFE in low proficiency bilinguals, while this effect was absent in highly proficient bilinguals. The eye-tracking (ET) data showed late coactivation of low-PO words and, surprisingly, no coactivation of high-PO words in low proficiency bilinguals. Highly proficient bilinguals showed no clear pattern of language coactivation in the ET data. The English monolingual control group showed no effects during the critical time window. Conclusions: These results are interpreted within the framework of L2 processing models. At low levels of proficiency, the PO between translations facilitates access to meaning. On the other hand, highly proficient bilinguals no longer benefit from the PO between translations, at least for concrete and simple nouns. Originality: The findings demonstrate a clear CFE in auditory comprehension. Proficiency in L2 and PO modulated the effect, as shown in both the response time and in the ET data, respectively. Implications: These findings suggest that at low levels of L2 proficiency, learners more easily access the conceptual information if the auditory input is similar to their native language. Nevertheless, as proficiency increases, this facilitation disappears.